FINANCIAL LITERACY, SOCIAL INFLUENCE, AND SAVING BEHAVIOR AMONG MICRO AND SMALL BUSINESS OWNERS: THE MODERATING ROLE OF SELF-CONTROL - Aunurrafiq, Aunurrafiq; Kamaliah, Kamaliah; Badriyah, Nurul; Rifqi, Ahmad (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2026)
Among micro and small businesses, business actors have problems in saving, especially when dealing with tighter business conditions, and financial knowledge is limited. For micro and small business owners, saving behavior is a crucial mechanism for coping with income volatility and ensuring financial sustainability, rather than merely a matter of individual preference. The study aims to analyze the effects of financial literacy and social influence on saving behavior, with self-control as a moderating variable among MSME entrepreneurs. A quantitative study was conducted from August to October 2025 to collect data using a structured survey with a sample of 183 MSMEs in Siak. The data were analyzed using a moderated regression model. The study shows that financial literacy and social influence significantly and positively impact saving behavior. Furthermore, self-control serves as a moderating variable, enhancing the relationships between financial literacy and saving behavior, as well as between social influence and saving behavior. This shows that higher self-control improves MSME actors' ability to apply financial knowledge and respond more effectively to social influence. Given these findings, the study highlights the need to incorporate self-control training in financial education and to use social frameworks to improve saving behavior among MSME entrepreneurs.